A light-gated potassium channel for sustained neuronal inhibition. (November 2018) - Alberio, Laura; Locarno, Andrea; Saponaro, Andrea; Romano, Edoardo; Bercier, Valérie; Albadri, Shahad; Simeoni, Federica; Moleri, Silvia; Pelucchi, Silvia; Porro, Alessandro; Marcello, Elena; Barsotti, Noemi; et al.
Abstract Currently available inhibitory optogenetic tools provide short and transient silencing of neurons, but they cannot provide long-lasting inhibition because of the requirement for high light intensities. Here we present an optimized blue-light-sensitive synthetic potassium channel, BLINK2, which showed good expression in neurons in three species. The channel is activated by illumination with low doses of blue light, and in our experiments it remained active over (tens of) minutes in the dark after the illumination was stopped. This activation caused long periods of inhibition of neuronal firing in ex vivo recordings of mouse neurons and impaired motor neuron response in zebrafish in vivo. As a proof-of-concept application, we demonstrated that in a freely moving rat model of neuropathic pain, the activation of a small number of BLINK2 channels caused a long-lasting (>30 min) reduction in pain sensation. BLINK2 is a light-activated potassium channel for optogenetic inhibition of neuronal activity. Alberio et al. apply the tool in systems as diverse as cultured rat neurons, mouse brain slices, behaving zebrafish and a rat model of neuropathic pain.